Pemahaman Msyarakat Kecamatan Baranti Terhadap Hoax di Media Sosial (Perspektif Hukum Islam) - Basri, Rusdaya (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2019)
The research about the understanding of the Baranti Districk community on hoaxes the social media perspective of islamic law. Based on the main sources of islamic teachings, namely the Qur'an, hadist, and the result of the Ulama's Fatwa about hoaxes. In general, the Baranti distric community of Sidrap said reader on the social media intelligent and wise, this is based with understanding and knowledge of their depth of hoaxes spread on social media and how to recignize where the news hoax and where the news is true, and how to anticipate when the receive hoaxes any time become a communication for holders of android phones in the Baranti Districk of Sidrap. Religious figures play an important role in providing an understanding of the dangers of hoaxes on social media, because the Ustadz or Dai is community figure who is trusted by the community.